FATTY ACID COMPOSITION OF THREE SPECIES OF FRESH WATER FISHES. - GOPAKUMAR, K (Fishery Technology, 2017)
Fatty acid composition of freshwater fish tilapia, (Tilapiamosamhica), barbus (Barbus carnaticus) and Varal (Ophicephalus)is determi:1ed by gas-liquid chromatography.Var:ll contained the highest amount of c20:5 acid comparedto other two species. Of the odd-numbered fatty acidsc17 was the predominant fatty acid present. Palmitic acidwas found to be in a lower level in these fish species comparedto marine fish.Barb us recorded unusually high percentage of 23.3% ofc18 :2 Acid.